Influence of Rice Husk Biochar and Coffee Husk Biochar Aplication on P and Zn Nutrient and The Growth of Rice Plants in Paddy Soil with High Total P - Satber Naibaho; Hamidah Hanum; Ir. Supriadi (Jurnal Agroekoteknologi, 2018)
This study aims to evaluate the effect of  rice husk biochar and coffee husk biochar, to evaluate difference effect of rice husk biochar and coffee husk biochar and to know  effect of difference dose of rice husk biochar and coffee husk biochar on phosphate and zinc, and  rice growth in the paddy soil with high total P. The research was conducted on the greenhouse, Faculty of Agriculture, University of North Sumatra, Medan. The soil which used from the paddy soil in Lubuk Dendang, Perbaungan, Serdang Bedagai which has the high total P. The experiment was carried out using completely randomized design with 7 treatment : Control; 10 ton/ha rice husk biochar; 20 ton/ha rice husk biochar; 30 ton/ha rice husk biochar; 10 ton/ha coffee husk biochar; 20 ton/ha coffee husk biochar; 30 ton/ha coffee husk biochar. The Analysis of data used the analysis of variance and contrast orthogonal test.Experimental results showed that rice husk biochar and coffee husk biochar  has significant effect on  levels of Zn plant, but not significant effect on soil pH, available P, soil Zn HCl 25%, levels of P plant, P uptake, Zn uptake and the growth of plants. Coffee husk biochar has more potential than rice husk biochar to increasing levels of Zn plant. Dose of coffee husk biochar 20-30 ton/ha increasing levels of Zn plant higher than 10 ton/ha. Keyword : biochar, coffee husk, P, rice husk, Zn